1992
DOI: 10.1073/pnas.89.21.10036
|View full text |Cite
|
Sign up to set email alerts
|

Insulitis in transgenic mice expressing tumor necrosis factor beta (lymphotoxin) in the pancreas.

Abstract: Tumor necrosis factor 13 (TNF-P) (lymphotoxin) may play an important role in the immune response and pathologic inflammatory diseases. Insulitis is an important early step in the development of insulin-dependent diabetes mellitus. To understand better the role of TNF-fl in the regulation of infamation and type 1 diabetes, we produced transgenic mice in which the murine TNF-fi gene was regulated by the rat insulin H promoter. The transgene was expressed in the pancreas, kidney, and skin of transgenic mice. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
88
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(92 citation statements)
references
References 21 publications
4
88
0
Order By: Relevance
“…Additionally, FLS exposed to LT␤ show induction of inflammatory chemokines, namely CCL5, CCL2, and CXCL8 (Figure 6), which elicit vigorous chemotactic responses of T cells (Figures 7 and 8). Similar LT␤-mediated up-regulation of chemokines and adhesion molecules has been shown in a variety of tumor cells lines, endothelial cells, and FDCs (24)(25)(26)(27)(28) and in the induction of chronic inflammation and lymphoid development in transgenic animals (24,(29)(30)(31)). The precise molecular pathway for the LT␣1␤2-mediated induction of chemokines and adhesion molecules is not yet known.…”
Section: Discussionsupporting
confidence: 63%
“…Additionally, FLS exposed to LT␤ show induction of inflammatory chemokines, namely CCL5, CCL2, and CXCL8 (Figure 6), which elicit vigorous chemotactic responses of T cells (Figures 7 and 8). Similar LT␤-mediated up-regulation of chemokines and adhesion molecules has been shown in a variety of tumor cells lines, endothelial cells, and FDCs (24)(25)(26)(27)(28) and in the induction of chronic inflammation and lymphoid development in transgenic animals (24,(29)(30)(31)). The precise molecular pathway for the LT␣1␤2-mediated induction of chemokines and adhesion molecules is not yet known.…”
Section: Discussionsupporting
confidence: 63%
“…The role of LT in the context of lymphoid neogenesis, development of autoimmune diseases and inflammatory disorders was further investigated in vivo (Picarella et al, 1992;Kratz et al, 1996;Luther et al, 2000;Drayton et al, 2003Drayton et al, , 2006Gommerman and Browning, 2003;Martin et al, 2004;Heikenwalder et al, 2005Heikenwalder et al, , 2008Haybaeck et al, 2009). These studies revealed that ectopic LT expression suffices to generate lymphoid-like structures (Picarella et al, 1992;Kratz et al, 1996;Gommerman and Browning, 2003;Heikenwalder et al, 2005;Haybaeck et al, 2009), also termed tertiary lymphoid organs or tissues.…”
Section: Lt and Inflammationmentioning
confidence: 99%
“…These studies revealed that ectopic LT expression suffices to generate lymphoid-like structures (Picarella et al, 1992;Kratz et al, 1996;Gommerman and Browning, 2003;Heikenwalder et al, 2005;Haybaeck et al, 2009), also termed tertiary lymphoid organs or tissues. LTa or LTab expression under the control of the rat insulin promoter II (RIP) induces chemokine expression and follicular lymphocytic infiltrations with mature follicular dendritic cell networks, resulting in chronic insulitis and glomerulonephritis (Picarella et al, 1992;Kratz et al, 1996;Drayton et al, 2003). Inflamed sites in RIPLTa or RIPLTab mice are vascularized with endothelia showing morphologic characteristics of high endothelial venules (Picarella et al, 1992;Cuff et al, 1999;Drayton et al, 2003).…”
Section: Lt and Inflammationmentioning
confidence: 99%
See 1 more Smart Citation
“…In studies that began before the Chaplin laboratory report, Ruddle and colleagues (19) had shown using transgenic mice that LTa was sufficient to promote lymphocyte-rich infiltrates in nonlymphoid tissue. Later, using more refined anatomical assessments, they observed that the infiltrates took on many of the organized features of a lymphoid tissue, indicating that LTa was sufficient to induce lymphoid neogenesis (20).…”
mentioning
confidence: 99%